ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS PENGGUNA JASA MASKAPAI CITILINK DI INDONESIA DENGAN METODE SEM-PLS - Rafael Farouk (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study means to dissect the variables impacting client dedication to Citilink carrier administrations in Indonesia utilizing Primary Condition Displaying (SEM) with a Fractional Least Squares (PLS) approach. Price, service quality, trust, and customer satisfaction were all identified as potential determinants of customer loyalty in this study. Purposive sampling was used to select 100 respondents for the sample. In order to investigate the connections that exist between these variables, the research employed a method known as partial least squares (PLS) and structural equation modeling (SEM). Information were gathered through a poll conveyed to respondents who are clients of Citilink carrier administrations. In view of the examination, the investigation discovered that the cost variable affects client steadfastness. The trust variable demonstrates a positive and significant influence on customer loyalty. The service quality variable has a positive and significant impact on loyalty. Loyalty is influenced positively and significantly by the satisfaction variable